2020
DOI: 10.1039/d0fo02502j
|View full text |Cite
|
Sign up to set email alerts
|

Bovine plasma hydrolysates’ iron chelating capacity and its potentiating effect on ferritin synthesis in Caco-2 cells

Abstract: Bovine plasma hydrolysates with a degree of hydrolysis of 19.1% have an iron chelating capacity of 38.5 ± 0.4% and increase the synthesis of ferritin in Caco-2 cells five-fold compared to the control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…The result showed that a decrease in the molecular weight leads to an increase in the AC, and FBPH-3 was the fraction that showed the greatest AC (see Table 2). It is possible that the AC of peptides from BP are more active and stable when they have peptide bonds in their structure, rather than having single amino acid residues or dipeptides (Gómez-Grimaldos et al 2020). These results are consistent with some studies which have obtained low molecular weight peptides with elevated AC (Gómez and Zapata 2016;Wiriyaphan et al 2015).…”
Section: Separation Of Antioxidant Peptides From Bphsupporting
confidence: 90%
See 3 more Smart Citations
“…The result showed that a decrease in the molecular weight leads to an increase in the AC, and FBPH-3 was the fraction that showed the greatest AC (see Table 2). It is possible that the AC of peptides from BP are more active and stable when they have peptide bonds in their structure, rather than having single amino acid residues or dipeptides (Gómez-Grimaldos et al 2020). These results are consistent with some studies which have obtained low molecular weight peptides with elevated AC (Gómez and Zapata 2016;Wiriyaphan et al 2015).…”
Section: Separation Of Antioxidant Peptides From Bphsupporting
confidence: 90%
“…Likewise, peptides separated by ultrafiltration with considerable AC and with low molecular sizes between 1 and 5 kDa have also been observed in the literature (Wiriyaphan et al 2015). When hydrolyzed, protein origin substances release amino acids, which are known for their ability to donate electrons such as tryptophan (Try), tyrosine (Tyr), and histidine (His), which increase AC when exposed by hydrolysis processes and are contained in BPH in concentrations between 3.3 ± 0.02 to 28.7 ± 0.3 mg/g of protein (Gómez-Grimaldos et al 2020).…”
Section: Separation Of Antioxidant Peptides From Bphmentioning
confidence: 79%
See 2 more Smart Citations
“…The poor absorption efficiency of non-heme iron in vivo is due to its low solubility [36]. The carboxyl, hydroxyl and amino groups of amino acids and peptides increase the solubility of non-heme iron in combination with it [18,37]. For example, a heptapeptide (SVNVPLY) derived from barley spontaneously formed complexes with non-heme iron, and then significantly increased iron absorption in Caco-2 cells compared to ferric sulfate [38].…”
Section: Discussionmentioning
confidence: 99%